Bioactivity of Kemangi (Ocimum sanctum L.) Flower Infusa Against Candida albicans In Vitro - Tri Purnami Dewi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: The surface of acrylic resin denture, which attaches to the oral mucosa, has microporosity, a place for bacterial plaque and Candida albicans to accumulate if not cleaned properly. An increase in Candida albicans colonies on the surface of dentures can cause denture stomatitis. Dentures can be cleaned mechanically with a soft-bristled brush, or chemically using cleaning agents. Denture cleaning materials on the market are sold in limited quantities at expensive prices. Natural ingredients can be alternative denture cleaning agents. This study aims to determine the difference in the bioactivity of basil and green betel leaf infusion on the growth of Candida albicans in vitro. Materials and Methods: This research is a laboratory experimental study using a post test only control group design method, divided into 4 groups, group 1 as a negative control using aquadest, group 2 as a positive control using polident denture cleanser, group 3 using 50% green betel leaf infusa, and group 4 using 50% basil leaf infusa. Each group consisted of 6 acrylic resin plates as a medium for Candida albicans attachment. Differences in the mean number of colonies in the groups were analyzed using Mann-Whitney test. Results and Discussions: Statistical analysis showed that there was a significant difference in the mean number of colonies between all groups regarding the growth of Candida albicans colonies with a p-value of 0.001 (p < 0.05). Conclusion: The results showed that basil leaf infusion had lower bioactivity potential than green betel leaf infusion against Candida albicans in vitro.